Security of Storage in Carbon Dioxide Enhanced Oil Recovery. (July 2017) - Stewart, R Jamie; Johnson, Gareth; Haszeldine, Stuart; Olden, Peter; Mackay, Eric; Mayer, Bernhard; Shevalier, Maurice; Nightingale, Michael
Abstract: The Pembina Cardium CO2 Monitoring Pilot was used as a test site to determine the relative roles of trapping mechanisms. Two methods to assess this distribution are presented. A geochemical approach using empirical data from the site was used to determine the phase distribution of CO2 at a number of production wells that were sampled monthly during a two-year CO2 injection pilot. In addition, a simplified reservoir simulation was performed. Results indicate that significant amounts of CO2 are stored in the oil phase thus reducing the amount of CO2 available as a buoyant free phase and hence increasing storage security.